Alfred Zimmern’s early political thought II: liberalism, Burke, and the Greek Commonwealth - Rood, T (Imprint Academic, 2024)
This is the second of two articles analysing the intellectual formation of Alfred Zimmern, a leading figure in the study of International Relations in the first half of the twentieth century. Drawing on many archival sources, it argues against claims in recent scholarship that Zimmern should be classified as a Burkean liberal. It first outlines Zimmern’s frequent advocacy of Socialism and state intervention, and then examines the politics of Zimmern’s famous monograph The Greek Commonwealth (1911), suggesting that the influence of Aristotle and Anthropology, and not just Burke, can be seen in his portrayal of the power of tradition in early Greece, and that this traditionalism is presented as preparing for the revolutionary freedom claimed for the classical polis.